Desensitization of cAMP Accumulation via Human β3-Adrenoceptors Expressed in Human Embryonic Kidney Cells by Full, Partial, and Biased Agonists - Okeke, Katerina; Michel-Reher, Martina B.; Gravas, Stavros; Michel, Martin C. (Frontiers in Pharmacology, 2019)
β3-Adrenoceptors couple not only to cAMP formation but, at least in some cell types, also to alternative signaling pathways such as phosphorylation of extracellular signal-regulated kinase (ERK). β3-Adrenoceptor agonists are used in long-term symptomatic treatment of the overactive bladder syndrome; it is only poorly understood which signaling pathway mediates the clinical response and whether it undergoes agonist-induced desensitization. Therefore, we used human embryonic kidney cells stably transfected with human β3-adrenoceptors to compare coupling of ligands with various degrees of efficacy, including biased agonists, to cAMP formation and ERK phosphorylation, particularly regarding desensitization. Ligands stimulated cAMP formation with a numerical rank order of isoprenaline ≥ L 755,507 ≥ CL 316,243 > solabegron > SR 59,230 > L 748,337. Except for the weakest agonist, L 748,337, pre-treatment with any ligand reduced cAMP responses to freshly added isoprenaline or forskolin to a similar extent. On the other hand, we were unable to detect ERK phosphorylation despite testing a wide variation of conditions. We conclude that a minor degree of efficacy for cAMP formation may be sufficient to induced full desensitization of that response. Transfected human embryonic kidney cells are not suitable to study desensitization of ERK phosphorylation by β3-adrenoceptor stimulation.